Analysis of Strenghts, Weakness, Opportunity, Threat (Swot) In Determining The Marketing Strategy of Deposits Products - Mabrurrosi, Mabrurrosi (International Conference on Islamic Economic (ICIE), 2022)
This study focuses on two issues. First, what are the strengths, weaknesses, opportunities, and threats in KSPPS Nuri Cabang Pegantenan?. Second How is the storage product marketing strategy in KSPPS Nuri Brang Pegantenan? The purpose of this writing is first to know any strength, weakness, opportunity, and threat in KSPPS Nuri Brang Pegantenan. Second, know the strategy of marketing storage products in the face of competition in KSPPS Nuri Brang Pegantenan. This research subject is the manager, marketing funding, and customer survice at KSPPS Nuri Cabang Pegantenan. This study uses qualitative approaches and data collection procedures that are used: observation, interviews and documentation. Research has shown that, firstly, the strength, obtained the support of special members from members of the foreign alumni association around the location, employees already have an emotional bond between members of the cooperation, have some storage products, the application of the syariat system in its operational activities, pass an ISO certificate, Promotion activities using employees, print media, social bacteria, and have websites and online applications. Weakness is an SDM quality limitation that corresponds to the office to be filled in. Opportunities are, the provision of affordable retail services, many people from the alumni Pondok Pesantren, the open market market/strategic location due to market proximity, and Transactions using the company system. The threat is to collapse conventional banks and corporate finance institutions, not all of the public are aware of the importance of corporate cooperation, and the location of competitors is more strategic than in KSPPS Nuri Cabang Pegantenan. Once SWOT is known, then the position in the IE matrix is known which is in the V quadrant produces a strategy of consistency through horizontal integration... the two strategies that can be used are the SO Strategy is to increase the bonds that have been created, to enhance the activities in promoting KSPPS Nuri Cabang Pegantenan, giving training to improve the understanding of marketers. The WO strategy is to provide training against the colonists. The WT strategy is to determine a competitive price, and to socialize about the existence of KSPPS Nuri Cabang Pegantenan. The WT strategy is to improve SDM quality in KSPPS Nuri Cabang Pegantenan.